Retained Fetal Membranes in a Marwadi Mare: A Case Report - Kapadiya, FM; Suthar, VS; Patel, SC (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
Placenta has been defined as “An apposition between maternal and fetal tissue to establish physiological exchange” (Mossman, 1937). The review of the literature indicates that membranes should be considered as retained if they are not delivered within three hours of parturition, although there is no particular scientific basis to this time frame in mares. The etiology of this problem varies from abortion, dystocia, prolonged gestation, cesarean section, fetotomy, hydropsy, induced delivery to many other plausible factors (Provencher et al., 1988; Frazer, 2003; Parmar et al., 2018). A retained fetal membrane (RFM) is the most common postpartum problem in draft mares (Cuervo-Arango and Newcombe, 2009; Dinuka et al., 2018); however, the reported incidence of RFM in Marwadi mares is rare, and recently it was published in a Kathiawadi mare (Patel et al., 2018). It is well documented that RFM is a medical emergency as far as risks of metritis, laminitis, fertility are concerned. In extreme cases, it also leads to death. Therefore, different treatment regimens such as oxytocin, antimicrobial therapy, uterine lavage, Burne’s technique, etc. were developed by practitioners and practiced globally to solve the issue (Provencher et al., 1988; Coutinho da Silva, 2016).